Influence of Gerda’s Character in Supporting Einar’s Transition into Lili in The Danish Girl Film - Septi Herlinda; Sholikatus Sa'diyah (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This research aims to show how Gerda Wegener, as a supporting character in The Danish Girl film, could significantly contribute to the main character’s transition from Einar Wegener (male) to Lili Elbe (female) through Gerda’s character and personality depicted in the film. This research uses the descriptive qualitative method. The writer uses the theory of the Big Five personality factors, characterization, and altruism to support the analysis. This research shows that Gerda’s character and personality are the leading cause of the conflict that occurred in the film, on how the main character, Einar Wegener, overcame his gender dysphoria to transform into a woman named Lili Elbe fully. Based on the Big Five personality factors, this research discovered that; Gerda’s personality in agreeableness and openness are highly relatable in influencing Lili’s transition. Moreover, Gerda’s behavior in altruism is also found to be the main reason she chose to support the main character’s gender transition despite the massive loss upon her. In conclusion, Gerda Wegener, as a supporting character, played the most significant role in stirring the plot by her influence in supporting Einar Wegener’s gender transition. It also shows that someone can be so selfless regarding the person they adore. Finally, it gives a new perspective on how significant the role of supporting characters is in a film based on their character and personality.